Teodoro M. Kalaw an annotated bio-bibliography, 1901-1974 - Godoy, Ester Orencia; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1975)
This is an annotated bio-bibliography of the works by and about the late Honorable Teodoro M. Kalaw covering the period 1901-1974, in the form of theses, manuscripts, books, serials, typescripts, documents and periodical articles. This work attempts to preserve in one volume the scattered materials both published and unpublished. The 225 entries are grouped under Part A - Works of Teodoro M. Kalaw, Part B - Works by him published posthumously, and Part C - Works written about him. A brief annotation is given for each of the items to provide the researcher an idea of its subject matter. Title and subject indexes have been provided to facilitate the location of specific items.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Kalaw, Teodoro Mangulat--Bibliography.